2020
DOI: 10.3802/jgo.2020.31.e64
|View full text |Cite
|
Sign up to set email alerts
|

Survival implication of lymphadenectomy in patients surgically treated for apparent early-stage uterine serous carcinoma

Abstract: Objective Uterine serous carcinoma (USC) is a rare highly aggressive disease. In the present study, we aimed to investigate the survival implication of the systematic lymphadenectomy in patients who underwent surgery for apparent early-stage USC. Methods Consecutive patients with apparent early-stage USC surgically treated at six Italian referral cancer centers were analyzed. A comparison was made between patients who underwent retroperitoneal staging including at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
5
23
0
Order By: Relevance
“…Casarin et al found that systematic lymph node dissection has important survival significance for patients, and the presence of lymph node metastasis was the main adverse prognostic factor [18]. Mean- while, it was found that preoperative imaging techniques such as magnetic resonance imaging (MRI) can improve the accuracy of hysteroscopy biopsy [19].…”
Section: Discussionmentioning
confidence: 99%
“…Casarin et al found that systematic lymph node dissection has important survival significance for patients, and the presence of lymph node metastasis was the main adverse prognostic factor [18]. Mean- while, it was found that preoperative imaging techniques such as magnetic resonance imaging (MRI) can improve the accuracy of hysteroscopy biopsy [19].…”
Section: Discussionmentioning
confidence: 99%
“…Positive nodes were independently associated with worse disease-free survival (DFS) and disease-specific survival (DSS), while adjuvant chemotherapy significantly improved DFS. However, at Cox regression analysis, lymphadenectomy did not significantly influence DFS (p=0.09) and DSS (hazard ratio=0.14; 95% confidence interval=0.02-1.21; p=0.07) [22]. Only 25 patients (24%) had complete retroperitoneal staging including the removal of both pelvic and para-aortic lymph nodes, while 76% underwent only systematic pelvic LNE [22].…”
mentioning
confidence: 92%
“…In the very interesting paper "Survival implication of lymphadenectomy in patients surgically treated for apparent early-stage uterine serous carcinoma" Casarin and colleagues [22] have compiled the data from 140 consecutive patients with apparent early stage serous EC treated at 6 Italian referral centers. One hundred six patients had at least pelvic LNE and 34 had no lymph node dissection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Primary mucinous carcinomas of the endometrium comprise 1–9% of all ECs, usually showing an endocervical-type differentiation [ 5 , 6 ]. They are typically well-differentiated with a relatively good prognosis; however, aggressive cases have been reported [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%